Evaluation of bacterial inoculants for yield enhancement of white button mushroom, Agaricus bisporus under commercial scale cultivation - Ahlawat, o P; Manikandan, K (Mushroom Research, 2016)
The study presents the effect of bacterial inoculants added in button mushroom compost at spawning and in casing at casing stage on fruit body yield of Agaricus bisporus and other related parameters using four different casing materials. Adding of Alcaligenes faecalis at casing in farm yard manure (FYM) + spent mushroom substrate (SMS) and FYM based casing materials gave higher fruit body yield during all three cultivation trials performed during three consecutive seasons. Inoculation of FYM + SMS based casing with broth cultures of two different strains of Bacillus subtilis also gave higher fruit body yield of A. bisporus. The multi-location trial conducted at six different centres of All India coordinated Research Project on Mushroom with four different casing materials also proved the stimulatory effect of A. faecalis inoculations on fruit body yield. The A. faecalis inoculated casing materials giving higher fruit body yield were also found to harbor 2 to 7 folds higher population of bacteria and fungi at first flush stage. The fruit body yield enhancement was found to be contributed by the involvement of microbial factor rather than the nutrients and moisture contributed by the A. faecalis multiplying medium. The study has relevance for A. bisporus yield enhancement under commercial scale cultivation.Â